THE ROLE OF DIGITALIZATION IN ENHANCING AUDIT EFFICIENCY AND ACCURACY - Zakhidov Dilshodbek (Web of Journals Publishing, 2024)
This article explores the impact of digitalization on the audit process, focusing on the efficiency, accuracy, and transparency achieved through digital tools. Leveraging automated data processing and decision-support systems, digital auditing methods enable auditors to manage large datasets, minimize human error, and improve compliance with international standards. Through a study of data analytics and digital tools used in auditing, this paper presents findings on how digitalization enhances audit quality and provides recommendations for integrating technology in audit practices.
Keywords: Digitalization, audit process, automated data processing, audit quality, data analytics, compliance, risk management.